Legal Protection of Traditional Medicines Against Biopiracy and Misappropriation: Ensuring Fair Benefit Sharing for Local Communities - Yuliati Yuliati; Hanif Nur Widhiyanti; Ayu Mustika Pamungkas (Universitas Sebelas Maret, 2026)
Indonesia possesses rich traditional medicinal knowledge that has been transmitted across generations and constitutes an essential part of local communities’ cultural heritage. However, the modern commercial use of traditional medicines often occurs without fair benefit-sharing, leading to practices such as biopiracy and misappropriation. This research examines the adequacy of Indonesia’s legal framework in protecting traditional medicines against such exploitative practices. The findings demonstrate that despite Indonesia’s ratification of various international instruments—including the Convention on Biological Diversity, the TRIPs Agreement, and the Nagoya Protocol—legal protection for traditional medicinal knowledge remains fragmented and insufficient. Existing national regulations, particularly Law Number 36 of 2009 on Health and the Patent Law, provide only limited and indirect protection. Patent-based protection is difficult to apply due to the requirements of novelty and inventive steps, which are incompatible with the communal and hereditary nature of traditional knowledge. Although Article 26 of the Patent Law acknowledges traditional knowledge, it fails to offer comprehensive protection or ensure equitable benefit-sharing for local communities. This study concludes that Indonesia urgently requires a specific sui generis or umbrella legal framework to protect traditional medicines against biopiracy and misappropriation while ensuring justice, legal certainty, and fair distribution of benefits.